(untitled) (Psicologia USP, 2011)
Feeding is a complex object of study that involves many scientific areas. The goal of this research is to understand the meaning and the emotional experiences of feeding for mothers with daughters suffering from eating disorders. The theory was based on qualitative, descriptive and exploratory research. Five mothers of young people who suffer from eating disorders took part in this study and attended meetings to have psychological support at Grupo de Assistência em Transtornos Alimentares do Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto (GRATA-HCFMRP-USP) during the year of 2008. A semi-structured guide was used as an instrument to collect the data, and the interviews were recorded and written out verbatim. From the data analysis, it is thought that the difficulties these mothers have concerning feeding and the bonds built from the relation to their own mothers tended to be repeated with their daughters. The study suggests the existence of heritage that preceded them and crossed generations.